Goya's deafness. Issue 6 (17th November 2008) - Smith, P E M; Chitty, C N; Williams, G; Stephens, D
Abstract : Francisco Goya (1746–1828), a major Spanish artist, became profoundly deaf aged 46 years, following an acute illness. Despite this, his success continued and he eventually died aged 82 years. His illness is sketchily documented in letters written during his convalescence, describing headache, deafness, tinnitus, unsteadiness and visual disturbance with recovery (apart from deafness) over three months. There was a milder similar illness two years before, suggesting a relapsing condition. Vogt–Koyanagi–Harada syndrome, although previously accepted as Goya's diagnosis, is not supported by the limited evidence. Susac's syndrome or Cogan's syndrome, although both rare, are more likely explanations.